Reflecting the Effectiveness of Yogyakarta City Government's Policies in Creating a Smoke-Free Zone - Andini, Hafizien Sastri; Syakdiah, Syakdiah; Kusumawiranti, Retno (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2022)
The responsibility of the State and the regions in carrying out the constitutional mandate that guarantees a healthy living environment is carried out by the Yogyakarta city government through the implementation of the Yogyakarta City Regional Regulation No. 2 of 2017 concerning non-smoking areas, the City Hall environment has not gone well, because there are still violations committed by visitors by smoking in any place. Even though the City Government has provided three smoking areas. The implementer already has compliance with the implementation of a smoke-free area by implementing this program as well as possible. But not with people who still can't follow and apply the rules of this no-smoking area. The effectiveness of implementing a smoke-free area is still not running as it should, this is due to various obstacles and obstacles in implementing a smoke-free area, namely community compliance and participation. The call for a smoke-free area is still underestimated by the public. The lack of community participation in implementing a smoke-free area has made implementers think of other ways to implement this program. The level of community compliance is also very low due to the lack of public awareness of the importance of implementing this smoke-free area.  Key words : Application, Non-Smoking Area, Yogyakarta